2016
DOI: 10.3390/ijms17010107
|View full text |Cite
|
Sign up to set email alerts
|

Erdr1 Suppresses Murine Melanoma Growth via Regulation of Apoptosis

Abstract: Melanoma, one of the aggressive cancers, is known to be resistant to chemotherapy. Because of its aggressive nature, effectively inducing apoptosis is necessary to treat melanoma. Erythroid differentiation regulator 1 (Erdr1) is known to be a stress-related survival factor exhibiting anti-cancer effects in several cancers. However, little is known about the functions and underlying mechanisms of Erdr1 so far. To demonstrate the effect of Erdr1 in melanoma apoptosis, recombinant murine Erdr1 was injected into m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 20 publications
0
21
0
1
Order By: Relevance
“…A high concentration of Erdr1 has an inhibitory effect on growth of the BL-70 Burkitt lymphoma cell line, suggesting that Erdr1 regulates the homeostasis of cell growth [7]. Recently, the pro-apoptotic property of Erdr1 was confirmed by the demonstration that rErdr1 induces apoptosis of melanoma cells via modulation of apoptosisregulating factors, such as Bcl-2 and Bax [8]. In addition, recent studies suggest the anti-inflammatory property of Erdr1 in contrast to the pro-inflammatory effects of IL-18.…”
Section: Research Perspective: Immunologymentioning
confidence: 69%
“…A high concentration of Erdr1 has an inhibitory effect on growth of the BL-70 Burkitt lymphoma cell line, suggesting that Erdr1 regulates the homeostasis of cell growth [7]. Recently, the pro-apoptotic property of Erdr1 was confirmed by the demonstration that rErdr1 induces apoptosis of melanoma cells via modulation of apoptosisregulating factors, such as Bcl-2 and Bax [8]. In addition, recent studies suggest the anti-inflammatory property of Erdr1 in contrast to the pro-inflammatory effects of IL-18.…”
Section: Research Perspective: Immunologymentioning
confidence: 69%
“…Here, we determined the anti-migratory activity of Erdr1 in synovial fibroblasts. In addition, our previous study suggests a pro-apoptotic role of Erdr1 in mouse melanoma [8], implying that Erdr1 might act as a pro-apoptotic factor in synovial fibroblasts to inhibit hyperproliferation.…”
Section: Discussionmentioning
confidence: 99%
“…A high concentration of Erdr1 has an inhibitory effect on growth of the BL-70 Burkitt lymphoma cell line, suggesting that Erdr1 regulates the homeostasis of cell growth [7]. Recently, the pro-apoptotic property of Erdr1 was confirmed by the demonstration that rErdr1 induces apoptosis of melanoma cells via modulation of apoptosis-regulating factors, such as Bcl-2 and Bax [8]. In addition, recent studies suggest the anti-inflammatory property of Erdr1 in contrast to the pro-inflammatory effects of IL-18.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that melanoma is extremely resistant to chemotherapy because of the low apoptotic rate in the cancer cells [21]. Recently, the ERDR1 protein was found to enhance apoptosis in melanoma cells by regulating Bcl-2 and Bax expression, providing evidence for its critical role in the suppression of melanoma progression [22]. Lee et al confirmed that treatment with recombinant ERDR1 induces apoptosis via the downregulation of Bcl-2 and the upregulation of Bax in B16F10 cells in vitro [22].…”
Section: Erdr1 Expression and Apoptosis Controlmentioning
confidence: 99%